Image og the Teacher in Schools Websites – Representative of the School - Āriņa, Baiba; Strods, Raimonds (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Article consists of three parts - theoretical, empirical research and recommendations for improvement the school website photo galleries. Publication analyses ideas (Weber&Mitchell, Ķestere, Kaļķe, Fischer&Kiefer, Veide) that reveal importance of the teacher's image in the representation of the school, significance of the picture and selfpromotion in the school context. The empirical study consider teacher’s image in 17 Latvian school website photo galleries and surveys 102 primary school student’s parents to find out their views on the school website photo galleries impact on the selection of the school for their children. Analysis of the theoretical literature and interpretation of the results of the study highlights recommendations for the improvement of the school website photo galleries as a type of school's self-representation.